The Impact of Creativity and Intelligence on the Social Adaptation of the Students of the Faculty of Physical Education - Yakymchuk, Borys A.; Yakymchuk, Iryna P.; Vakhotska, Iryna O.; Sundukova, Irina V.; Lohvinova, Yaroslava O. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
In periods of social change, creativity is the leading resource for human adaptation. Therefore, in the learning process, it is important to provide for the development of creativity both as a professional skill and as a general life competence. This work aims to elucidate the features of the formation of creativity and intelligence of students in connection with their position in interpersonal relationships. We measured various creative abilities of 224 students of the Faculty of Physical Education (a set of tasks from the tests of creativity by Torrance and Guilford); general intelligence (Raven’s Progressive matrices) and sociometric status (Moreno’s method, the criteria of educational achievements, informal-emotional communication and sports team leadership were used). It is shown that in the learning process, students significantly increase the level of general intelligence, verbal and practical (everyday) creativity increases. The uneven dynamics of the manifestations of different types of creativity depending on the stage of learning was revealed: during periods of intense adaptation, a redistribution of cognitive efforts to achieve more significant and relevant goals was observed. Eight different types of combinations of creative abilities and general intelligence that determine the diversity of students’ adaptation strategies have been identified. Direct correlations and nonlinear relationships between the severity of various cognitive abilities and sociometric status are described. The balance of intellectual and creative processes, their effective use in various situations of interpersonal interaction is the key to gaining social authority.